The effects of Tai Chi exercise on body composition and cardiorespiratory fitness in Chinese university students with obesity: A quasi experiment study - Yali Xu; Feng Wang; Lei Yang; Wei Qiao; Hutkemri Zulnaidi; Annisaa Basar; Syed Kamaruzaman Syed Ali (Scientific Reports)
Abstract Obesity is an increasingly serious public health problem in China. This trend has surged in the population of university students and harmed their physical health. To identify the effects of Taichi exercise on lean body mass (LBM), waist circumference (WC), and maximal oxygen consumption (VO2max) for university students with obesity (USO). A total of 46 eligible participants were enrolled in this experiment, which involved a 12-week intervention. The participants had a mean age of 18.38 ± 0.73 years and a BMI of 31.50 ± 2.93. The sample consisted of 83.76% males and 16.24% females. LBM, WC, and VO2max were measured at both baseline and post-test. The instruments used included a body composition analyzer, measuring tape, and the VO2max formula. Data analysis was conducted using SPSS software. Tai Chi had a significant positive effect on WC, reducing it by 3.38 cm (P = 0.004, 95% CI, d = − 0.274), and on LBM, increasing it by 0.87 kg (P = 0.030, 95% CI, d = 0.081). However, it had no significant effect on VO2max, which increased by 1.7 mL/kg/min (P = 0.284, 95% CI, d = 0.326) in USO. Similarly, stretching exercises significantly reduced WC by 4.68 cm (P = 0.007, 95% CI, d = − 0.467) but had no significant effects on VO2max, which increased by 0.12 mL/kg/min (P = 0.991, 95% CI, d = 0.227), or on LBM, which increased by 0.40 kg (P = 0.547, 95% CI, d = 0.050) for USO. Additionally, there was no statistically significant difference between the Tai Chi and control groups in WC, VO2max, or LBM (p = 0.057) among USO. Besides of the significant positive effects on waist circumstance, Taichi exercise also shown optimism benefits on lean body mass. Taichi exercise is better than normal exercise on physical health for university students with obesity.